Vloga morale na področju pogodbenega prava - Drnovšek, Klemen (Podjetje in delo, 2015)
All general principles of the Slovenian Code of Obligations are based on morality. Therefore, morality is an important substantive source of contract law. Additionally, it is also a very important formal source. Primarily, morality is intended for the protection of general social interests and fundamental values. It also defines a fair relationship among contracting parties in the context of the principle of conscientiousness and fairness. Moral principles are particularly important as means of argumentation, therefore for the selection of the appropriate rule of law and for its interpretation. Morality also presents an important guideline on how to exercise the rights and individual agreements. A contract that contravenes moral principles shall be null and void. However, in milder cases, the result of disobedience should be sanctioned in the form of rejection of the request for legal protection. In commercial contracts, the role of morality is completely different due to the very nature of the relationship and circumstances under which the relationships are concluded. We are talking about the so-called business morality, which is based on good business customs. Nevertheless, the basic intention is the same, that is, to ensure humanity in relations between the parties also in the field of commercial contract law.
Keywords: etični vidik; pogodbe; pogodbeno pravo; poslovna etika